PENGARUH PIAGAM JAKARTA DALAM PEMBANGUNAN HUKUM NASIONAL PASCA PERUBAHAN UUD 1945 - Habloel Mawadi (Jurnal Program Pascasarjana Ilmu Hukum Universitas Islam As-Syafi'iyah, 2017)
The Jakarta Charter has a strong constitutional standing because it has beenstipulated by Presidential Decree no. 150 of 1959 concerning the Presidential Decreedated July 5, 1959 and published in the State Gazette of the Republic of Indonesia no.75 of 1959 and reinforced by the adoption of the MPR on the Fourth Amendment of the1945 Constitution on August 10, 2002. With such a strong constitutional standing,there is an obligation for Muslims and the state to implement Islamic Shari'ah inIndonesia as required by the Jakarta Charter. That is because, that the constitutionbinds all state institutions and all citizens. Therefore, the implementing constitution isall state institutions and all citizens in accordance with their rights and obligations asregulated in the 1945 Constitution. In Indonesia, as with other Muslim-majoritycountries, its empowerment has long since earned a decent place in the life of thecommunity along with the establishment of Islamic empires, and even once became theofficial law of the state. Nevertheless, Islamic law still exists, even if it is not complete.Sociologically and culturally, Islamic law never dies and even always present in thelife of Muslims in any political system, both colonialism and independence period andto the present day. But behind it all, Muslims actually experience various obstacles andobstacles in its efforts to transform Islamic Shari'ah into the national legal system. Itcan be done by making radical renewal of legal education, both in Islamic law andgeneral law covering the pattern and curriculum, so as to produce reliable, productive,responsive and anticipative legal scholars against the social development of society aswell as promoting dialogue, seminars and the like between Islamic law experts andtheir fellow men, and with the common law expert to find common vision andperception in order to build national law.